Theoretical Analysis of Entropy Generation at the Blade Interface of a Tubular Turbine Under Cooperative Conditions - Li, Zhenggui; Cheng, Chuang; Yan, Shengnan; Peng, Shengyang; Ma, Biao (Frontiers in Energy Research, 2021)
To study the influence of the blade entropy production range on the efficiency of a tubular turbine under coassociated conditions, the renormalization group K–ε turbulence model was used to simulate the full flow passage of the tubular turbine based on the Navier–Stokes equation, and the blade interface was analyzed using the eddy analysis method and entropy production theory. The results reveal that there is a strong correlation between the size of the high-entropy production area and the level of association. If the level of association is high, the size of the high-entropy production is small, and the turbine efficiency is high. Furthermore, if the level of association is low, the size of the high-entropy production area is large, and the turbine efficiency is low. Under small opening and small flow conditions, the blade entropy generation is due to the sharp change in the velocity gradient caused by the vortex on the blade. Under large opening and large flow conditions, the blade entropy production is mainly due to the friction loss caused by the impact of high-speed water flow.